Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Kerja Karyawan melalui Kepuasan Kerja sebagai Variabel Interverning (Studi pada BAN PAUD&PNF Provinsi Bali) - Wisudayanti, Ayu (Universitas Tabanan, 2025)
This research aimed to identify and analyze the influence of work performance, work environment, job satisfaction on the performance of assessors at BAN PAUD dan PNF Bali Province; identify and analyze the influence of work performance and work environment on job satisfaction of assessors at BAN PAUD dan PNF Bali Province; and identify and analyze the influence of work performance and work environment on performance through job satisfaction of assessors at BAN PAUD dan PNF Bali Province. This research used a quantitative approach focusing on hypothesis testing using measurable data and involving 83 assessors working at BAN PAUD dan PNF Bali Province. This research data came from primary data and secondary data using questionnaires and documentation. The results of this research showed that work performance had a positive and significant effect on assessor performance, work environment had a positive and significant effect on assessor performance, job satisfaction had a positive and significant effect on assessor performance, work performance had a direct positive and significant effect on assessor job satisfaction, work environment directly had a positive and significant effect on assessor job satisfaction, work performance indirectly had a positive and significant effect on assessor performance, work performance indirectly had a positive and significant effect on assessor performance through job satisfaction, and the work environment indirectly had a positive and significant effect on assessor performance through assessor job satisfaction.